Photochemistry - Schalk, Oliver, author 652532; Tapavicza, Enrico, author 652533; American Chemical Society (Online service) (Washington, DC : American Chemical Society, 2021)
Photochemistry is an important part of both chemistry and biology and is of great practical significance for the development of sustainable sources of energy. The mechanisms of photochemistry are far from trivial and far from understood. There are limits to how well theory can describe the processes and how well experiments can resolve them. This book aims to provide an overview of state-of-the-art methods for both theoretical development and experimental techniques, with a focus on ultrafast molecular processes and electronic excitation of organic molecules. These fields are active and progress is being made, carried by the increasing speed of computation and the development of new light sources, most notably X-ray sources at large facilities. Alongside these two layers of theoretical development and experimental techniques is a third layer—model building. In this layer, model building tries to find similarities in seemingly unrelated experimental results and deepen our general knowledge of photoinduced processes. Often, progress is made not by cutting-edge techniques but rather by using well-established techniques with a great variety of molecules—this approach promises less glory but is just as important as the first two layers. Examples mentioned in the text are the Woodward–Hoffman rules and the dynamophore concept. All three layers are crucial to push our knowledge further and, eventually, to use it for developing new and more advanced optical devices.